2023
DOI: 10.1097/spc.0000000000000640
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use disorder in cancer patients

Abstract: Purpose of reviewThe misuse of opioids has increased significantly in recent decades. Historically, cancer patients have not been considered at risk of opioid misuse. However, cancer pain is common, and opioids are often prescribed. Guidelines addressing opioid misuse often exclude cancer patients. Given that misuse is associated with significant harm and a reduction in quality of life, it is important to understand the risk of opioid misuse in cancer patients and how we can recognise and treat it. Recent find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Finally, the results of our study do not directly show that opioid‐limiting legislation was the reason for the decrease in opioid prescription duration in some states after 2016–2017, since causation cannot be determined from a national database study. Other factors may have contributed to the decline in opioids prescribed by otolaryngologists during this time period, including increased provider awareness, and scientific evidence of the hazards of opioid misuse as well the efficacy of alternative pain management strategies 23–26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the results of our study do not directly show that opioid‐limiting legislation was the reason for the decrease in opioid prescription duration in some states after 2016–2017, since causation cannot be determined from a national database study. Other factors may have contributed to the decline in opioids prescribed by otolaryngologists during this time period, including increased provider awareness, and scientific evidence of the hazards of opioid misuse as well the efficacy of alternative pain management strategies 23–26 …”
Section: Discussionmentioning
confidence: 99%
“…*p < 0.05; **p < 0.01. national database study. Other factors may have contributed to the decline in opioids prescribed by otolaryngologists during this time period, including increased provider awareness, and scientific evidence of the hazards of opioid misuse as well the efficacy of alternative pain management strategies [23][24][25][26].…”
mentioning
confidence: 99%
“…Expectedly, a large study conducted on the veteran population found that cancer patients were almost twice as likely to have an opioid prescription compared with noncancer patients [ 82 ]. These numbers raise a concern regarding the risk of developing opioid use disorders such as dependency or misuse among cancer patients and survivors [ 83 , 84 ].…”
Section: Prescription Opioids In Patients With Cancermentioning
confidence: 99%